Dendritic cell maturation assay for non-clinical immunogenicity risk assessment: best practices recommended by the European Immunogenicity Platform - Ackaert, Chloé; Gonzalez-Nolasco, Bruno; Rosenbaum, Marc; Perez-Olivares, Mercedes; Gutknecht, Michael; Ducret, Axel; Karle, Anette Christine (Frontiers in Immunology, 2025)
Early assessment and mitigation of non-clinical immunogenicity risk during early drug development is key for the development of safe and efficacious therapeutics. The dendritic cell (DC) maturation assay, one of the non-clinical immunogenicity risk assessment tools used in the drug development pipeline, investigates the ability of a test article to induce the maturation of immature monocyte-derived DCs, serving as an indicator of factors that may initiate an innate immune response and contribute to an adaptive immune response. These factors can be either intrinsic to the therapeutic’s mechanism of action and structure, or extrinsic from the final drug product, such as formulation components or contamination with host cell proteins or other impurities. Due to the nature of the assay, key parameters such as cell source, cell culture conditions, reagents, and assay-specific defined criteria for baseline response and positivity can differ amongst laboratories. In this manuscript, the specifics of this assay are discussed, key quality criteria for robustness are described, and the selection of appropriate controls to enable meaningful data interpretation are presented. The aim of conducting the DC maturation assay using best practices is to improve the assay to be fit-for-purpose and to facilitate comparability across projects and between laboratories.